Active players in resolution of shock/sepsis induced indirect lung injury: immunomodulatory effects of Tregs and PD‐1. Issue 5 (31st July 2014) - Tang, Lunxian; Bai, Jianwen; Chung, Chun‐Shiang; Lomas‐Neira, Joanne; Chen, Yaping; Huang, Xin; Ayala, Alfred
Abstract : PD‐1 immunomodulates Treg function in the resolution of indirect ALI, induced by shock/sepsis. Abstract : The immunomodulatory effects of PD‐1 and CD4 + CD25 + Tregs in the resolution of ALI are still poorly understood. Accordingly, 1 million Tregs were isolated from spleens of WT C57BL/6 or PD‐1 −/− mice (magnetical bead purification and subsequent labeling with/without Vybrant dye) and then AT into mice subjected to Hem shock during their resuscitation period, which were subsequently subjected to CLP/septic challenge (24 h post‐Hem) to induce iALI. Initially, we demonstrated that Vybrant‐labeled AT Tregs appear in the lungs of iALI mice. Subsequently, we found that AT of WT Tregs induced a significant repression of the indices of lung injury: a reduction of neutrophil influx to the lung tissue and a decrease of lung apoptosis compared with vehicle‐treated iALI mice. In addition, these mice had substantially higher concentrations of BALF and lung‐tissue IL‐10 but significantly decreased levels of lung KC. However, these beneficial effects of the AT of Tregs were lost with the administration of PD‐1 −/− mouse Tregs to the recipient WT mice. ALI was exacerbated in these recipient mice receiving AT PD‐1 −/− Tregs to the same extent as iALI mice that did not receive Tregs . These data imply that Tregs can act directly to modify the innate immune response induced by experimental iALI, and this is mediated, in part, by PD‐1. Hence, the manipulation of Tregs may represent a plausible target for treating iALI.